2004
DOI: 10.1111/j.1600-0749.2004.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

CTAB–Urea Method Purifies RNA from Melanin for cDNA Microarray Analysis

Abstract: Melanin represents a major problem for the study of melanoma by microarrays since it is retained during RNA extraction and inhibits the enzymatic reactions used for probe preparation. Here we report a new method for cleaning RNA from melanin, based on the use of the cationic detergent cetyl-trimethylammonium bromide (CTAB)-urea for RNA precipitation. This method is easy to perform and has a low cost. Purified RNA is recovered with high quality and good yield. CTAB-urea treated RNA from highly pigmented melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…At day 42, cells from all conditions were collected and genomic DNA was extracted. Since melanin pigment may interfere with DNA-and/or RNA-based molecular profiling 63 , we purified the samples using the OneStep TM PCR inhibitor Removal Kit (Zymo Research). The integrated sgRNAs were then amplified by PCR with primers containing multiplexing barcodes and adaptors and sequenced on the Illumina NextSeq500.…”
Section: Methodsmentioning
confidence: 99%
“…At day 42, cells from all conditions were collected and genomic DNA was extracted. Since melanin pigment may interfere with DNA-and/or RNA-based molecular profiling 63 , we purified the samples using the OneStep TM PCR inhibitor Removal Kit (Zymo Research). The integrated sgRNAs were then amplified by PCR with primers containing multiplexing barcodes and adaptors and sequenced on the Illumina NextSeq500.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the biopsies using QIAamp DNA Mini Kit ® (Qiagen, Chatsworth, CA, USA). Some of the DNA samples also had to undergo further steps to separate DNA from melanin [ 21 , 22 ]. DNA was dissolved in dH 2 O and kept at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, rice CBF2 was expressed in shoots and seeds but not in roots and leaves. Novillo et al [7,20] also reported that CBF2 is induced later than CBF1 and CBF3 during cold acclimation. Novillo et al [20] confirmed that nonacclimated and cold-acclimated CBF2 mutants have higher capacity for tolerating freezing and dehydration than the corresponding WT plants.…”
Section: Discussionmentioning
confidence: 94%
“…Arabidopsis CBF1, CBF2, and CBF3 are major transcriptional factors affecting cold-inducible gene expression [6,7]. CBF4 from Arabidopsis is weakly induced by cold stress [8], whereas DREB2A is induced by drought and salinity [9].…”
Section: Introductionmentioning
confidence: 99%